Meningkatkan Motivasi Berprestasi Rendah melalui Konseling Behavior Teknik Self-Management - Nurazmi, Rifky; Kurniawan, Kusnarto (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This research is based on the observation and interview with counselor of  SMK N 4 Semarang about low-achievement motive on 12th grade students of mechanical engineering 2 Semarang. The purpose of this study to describe the behavior counseling self-management techniques can improve student achievement motivation in the low-achievement motive mechanical engineering department at SMK Negeri 4 Semarang. Experimental research design of the study one-group pretest-posttest design, awarded to two students who have low achievement motivation. Methods of data analysis using descriptive data analysis and Wilcoxon percentage. The study found that there is a significant increase in achievement motivation in class XII student of mechanical engineering 2 between before and after a given treatment counseling technique of self-management behaviors. The counseling process is given in the meeting of 8 times each counselee. Picture of achievement motivation based on the calculation of descriptive analysis, it can be seen that the percentage before being given treatment, 50.5% of students R1 and R2 of 42.5% of students both in the low criteria. Meanwhile, after the treatment, 74% of students R1 included in the high criteria and students R2 of 63% included in the low criteria. This suggests that an increase of 23.5% at 20.5% of students R1 and students R2